Effectiveness, Patient Satisfaction, and Safety of a Next-generation PLLA Collagen Biostimulator for Nasolabial Fold Augmentation: 12-month Results of a Prospective Multicenter Study - Adriana Ribe; Ulrika Erhardt; Karina De Almeida Caramico; Émilie Souton-Al Gburi; Franco Grimolizzi; Per Hedén (Aesthetic Surgery Journal, 2026)
Abstract Background Poly-L-lactic acid (PLLA) dermal fillers induce neocollagenesis through a bioinductive mechanism rather than facial tissue volumization. The next-generation PLLA-LASYNPRO formulation (LASYNPRO, Lactic Acid Induced Synthesis of Collagen Protein), a biomaterial-microsphere technology developed for regenerative aesthetic biostimulation, composed of uniform, non-porous microspheres, has been proposed as an evolution of earlier PLLA products, offering a more controlled, lower-inflammatory regenerative pathway. Efficacy data for nasolabial fold (NLF) correction are emerging, but patient-reported outcomes remain underreported. Objectives To evaluate patient-reported outcomes, aesthetic self-perception, and treatment satisfaction over 12 months following JULÄINE (PLLA-LASYNPRO) treatment for NLF correction. Methods Prospective, single-arm, multicenter post-market clinical follow-up (PMCF) investigation enrolling 60 subjects. Subjects received up to 3 bilateral NLF injections of JULÄINE™ at 2- to 4-week intervals. Patient-reported outcomes included FACE-Q Appraisal of Lines (Nasolabial Folds), FACE-Q Satisfaction with Outcome, the Global Aesthetic Improvement Scale (GAIS), and a 12-item subject satisfaction questionnaire, assessed at 6 and 12 months after the final injection. Results At 12 months, the FACE-Q Appraisal of Lines score improved by a mean of 20.7 points (P<.0001; d=1.14), a large effect that continued to grow between 6 and 12 months. Subject GAIS responder rate was 83.3% at both timepoints. More than 90% of subjects reported natural-looking results; 83%–85% would repeat the treatment; 90%–94% would recommend it. Overall satisfaction was 88.9% at 6 months and 77.8% at 12 months. No serious adverse events or device deficiencies were reported. Conclusions JULÄINE produced sustained, clinically meaningful improvements in patient-perceived aesthetic outcomes with high treatment satisfaction over 12 months. The consistent perception of natural-looking results is in line with the progressive, collagen-building mechanism of PLLA-LASYNPRO.